2009
DOI: 10.3732/ajb.0900084
|View full text |Cite
|
Sign up to set email alerts
|

An experimental demonstration of the cost of sex and a potential resource limitation on reproduction in the moss Pterygoneurum (Pottiaceae)

Abstract: The cost of sexual reproduction is incurred when the current reproductive episode contributes to a a decline in future plant performance. To test the hypotheses that a trade-off exists between current sexual reproduction and subsequent clonal regeneration and that resources limit reproduction and regeneration, plants of the widespread moss Pterygoneurum ovatum were subjected to induced sporophytic abortion, upper leaf removal, and nutrient amendment treatments. Sexually reproducing plants were slower or less l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 61 publications
0
40
0
Order By: Relevance
“…Sexual reproduction and the production of sporophytes in mosses may be reduced by sperm-limitation [43,46], resource limitation [24,56,58,59], and abiotic stress ( [8]; Eppley et al [25]). Our experimental warming treatments increased sporophyte production in two moss species, P. alpinum and B. patens, compared with controls (Tables 2a and 3), and this warming potentially altered many steps in the process of sporophyte formation, from sperm and egg production, to gamete dispersal, to fertilization success, to sporophyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual reproduction and the production of sporophytes in mosses may be reduced by sperm-limitation [43,46], resource limitation [24,56,58,59], and abiotic stress ( [8]; Eppley et al [25]). Our experimental warming treatments increased sporophyte production in two moss species, P. alpinum and B. patens, compared with controls (Tables 2a and 3), and this warming potentially altered many steps in the process of sporophyte formation, from sperm and egg production, to gamete dispersal, to fertilization success, to sporophyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Since resources for metabolism and biomass gain are limited, increasing resource allocation to one function may reduce that to other functions (Bai et al, 2009;Liu et al, 2009). Reduced growth in response to increased sexual production has been known for many species (Snow and Whigham, 1989;Stark et al, 2009;Thiele et al, 2009). On the other hand, sometimes such a trade-off is not obvious (Liu et al, 2009;Thompson and Eckert, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Indeed several studies have since demonstrated greater sperm dispersal distances (for a review, see Glime, 2007), as well as stresstolerant sperm (Rosenstiel and Eppley, 2009;Shortlidge et al, 2012) and microarthropod-mediated sexual reproduction (Cronberg et al, 2006;Cronberg, 2012;Rosenstiel et al, 2012). Other factors can limit sexual reproduction in mosses, including: inadequate resources (Stark et al, 2000) growth trade-offs (EhrlĂ©n et al, 2000) and investment in environmental stress defence (Convey and Smith, 1993;Stark et al, 2009;Eppley et al, 2011). In Antarctic mosses, sporophyte formation appears to be restricted to all but the most favourable microsites (Seppelt et al, 1992), with most species relying primarily on vegetative (asexual) reproduction for dispersal and colonization.…”
Section: Introductionmentioning
confidence: 99%